Status prawny elektronicznej karty przekazania odpadów - Dmowska, Joanna Łucja (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
Waste records are an element of the waste management system, which not only reflects the achieved recovery and recycling targets, but also serves to monitor the flows with the possibility to identify the entities responsible for waste management at a given stage of ‘waste life’. Since the waste record is kept in the electronic system, its evidential and control importance is emphasized in relation to the possibility of monitoring the transferred and transported waste in real time. In this context, the electronic waste transfer card (e-KPO) has become an implementing object aimed at strengthening the system of restrictive sanctions as well as a means of proof and evidence in administrative proceedings, whose role has become more important in the waste management system.
Keywords: waste records; waste; BDO; proof; waste transfer note (KPO)